2021
DOI: 10.1080/21655979.2021.2012553
|View full text |Cite
|
Sign up to set email alerts
|

A novel circRNA-miRNA-mRNA network revealed exosomal circ-ATP10A as a biomarker for multiple myeloma angiogenesis

Abstract: The importance of angiogenesis in multiple myeloma (MM) is unquestionable; however, to date, the success of antiangiogenic therapies has been fairly limited. Exosomal circular RNAs (circRNAs) have been proven to be pivotal players in angiogenesis in various cancers. Nevertheless, their role in MM remains unknown. Therefore, we aimed to identify differentially expressed circRNAs in peripheral blood exosomes from MM patients and explore their diagnostic and prognostic values. We screened 2,052 circRNAs with sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 60 publications
0
20
0
Order By: Relevance
“…The expression of circ-ATP10A in patients with MM is significantly increased. Bioinformatics studies have found that circRNA-ATP10A can act as the sponge of hsa-miR-6758-3p/hsa-miR3977/hsa-miR-6804-3p/hsa-miR 1266-3p/hsa-miR-3620-3p and regulate downstream mRNA, thus upregulating the expression of VEGF-B, HIF-1α, platelet-derived growth factor A, and fibroblast growth factor to achieve angiogenesis in MM [ 67 ]. MM-Exos activate the EGF pathway in the bone microenvironment through rich double regulatory protein (amphiregulin, AREG), which leads to osteoclast formation.…”
Section: Oncologic Disease Environmentmentioning
confidence: 99%
“…The expression of circ-ATP10A in patients with MM is significantly increased. Bioinformatics studies have found that circRNA-ATP10A can act as the sponge of hsa-miR-6758-3p/hsa-miR3977/hsa-miR-6804-3p/hsa-miR 1266-3p/hsa-miR-3620-3p and regulate downstream mRNA, thus upregulating the expression of VEGF-B, HIF-1α, platelet-derived growth factor A, and fibroblast growth factor to achieve angiogenesis in MM [ 67 ]. MM-Exos activate the EGF pathway in the bone microenvironment through rich double regulatory protein (amphiregulin, AREG), which leads to osteoclast formation.…”
Section: Oncologic Disease Environmentmentioning
confidence: 99%
“…An experiment recognized a difference in the expression of circRNAs in exosomes from the blood of MM subjects for evaluating prognostic significance. These findings established that the levels of circ-ATP10A were remarkably increased in MM subjects [ 77 ]. The bioinformatics assessment indicated that circ-ATP10A can operate as a miRNA sponge and controls the concentrations of several growth factors, such as hypoxia-inducible factor-1alpha (HIF1A), platelet-derived growth factor subunit A (PDGFA), VEGFB, and fibroblast growth factor (FGF), while the circ-ATP10A concentration was correlated with BM microvessel density.…”
Section: Circrnas and Multiple Myelomamentioning
confidence: 75%
“…The bioinformatics assessment indicated that circ-ATP10A can operate as a miRNA sponge and controls the concentrations of several growth factors, such as hypoxia-inducible factor-1alpha (HIF1A), platelet-derived growth factor subunit A (PDGFA), VEGFB, and fibroblast growth factor (FGF), while the circ-ATP10A concentration was correlated with BM microvessel density. These effects were obtained by targeting miRNA-6758-3p/miRNA-3977/miRNA-6804-3p/miRNA-1266-3p/miRNA-3620-3p [ 77 ] ( Table 1 , Figure 3 ).…”
Section: Circrnas and Multiple Myelomamentioning
confidence: 99%
“…Similarly, exosomal circG042080 was identified as a possible predictor for MM-related myocardial damage 105 . Moreover, a recent paper found that exosomal circATP10A in MM patients had prognostic potential and correlated to VEGFB protein levels, suggesting involvement in angiogenesis 106 .…”
Section: Exosome Biomarkersmentioning
confidence: 96%